Unmet supportive care needs among head and neck cancer survivors beyond 5 years after diagnosis: a multinational cohort study - Jansen, Femke; Eerenstein, Simone EJ.; Taylor, Katherine J.; Amdal, Cecilie D.; Bjordal, Kristin; Astrup, Guro L.; Herlofson, Bente B.; Duprez, Fréderic; Gama, Ricardo R.; Jacinto, Alexandre A.; Hammerlid, Eva; Scricciolo, Melissa; et al. (The lancet. Regional health, 2025)
Background - This study investigates unmet supportive care needs (SCNs) among head and neck cancer (HNC) survivors beyond 5 years after diagnosis and examines the association with sociodemographic, clinical and lifestyle factors, and differences in European and non-European regions and healthcare systems. - Methods - In this cross-sectional study, 1097 HNC survivors from 11 countries completed the Short-Form Supportive Care Needs Survey (SCNS-SF34) and HNC-specific module (SCNS-HNC), encompassing physical and daily living, psychological, sexuality, HNC-specific and lifestyle domains. Scores were dichotomized per domain and across domains into moderate-high unmet SCNs (yes/no). Logistic regression analyses were used to investigate associated factors. - Findings - Half (50%, proportion 100/200) of HNC survivors had unmet SCNs (overall), especially unmet HNC-specific (40%, 40/100), psychological (25%, 25/100), and physical and daily living (22%, 22/100) needs. Personal (women, lower age), lifestyle (smoking, alcohol consumption) and clinical factors (advanced tumor stage, second primary tumor, multimodality treatment [versus single surgery], poor Karnofsky performance score and comorbidities) were associated with unmet SCNs. Physical and daily living, HNC-specific and overall unmet SCNs were more likely among survivors from Northern Europe compared to Southern and Western Europe. Unmet psychological, sexuality and lifestyle needs were more likely among non-European countries. All unmet SCNs (except psychological) were more likely among survivors with a national health system compared to a social and/or etatist health insurance system. - Interpretation - Half of HNC survivors have unmet SCNs. Insight into healthcare utilization may provide insights how to improve care. - Funding - European Organization for Research and Treatment of Cancer (EORTC) Quality of Life Group.